Diagnosis of surface water quality in Los Altos Norte region of Jalisco, Mexico - Castañeda Villanueva, Aldo Antonio; Flores López, Hugo Ernesto; Cuevas-Villanueva, Ruth Alfaro (Acta Universitaria, 2019)
Los Altos Norte region is located in the northeastern part of the state of Jalisco, within the Río Verde basin in the Lerma - Santiago hydrological region. In this region, the main product of the livestock sector is the table egg that represents 49.8% of the total production (2013). Much of the waste generated in the region by domestic, livestock and industrial activity is not properly managed, causing serious environmental deterioration. In the present work, the analysis of 20 sampling points of surface water distributed throughout the 8 municipalities that make up the region were compared on two occasions (2014 and 2016), detecting some degree of contamination in the studied bodies of water in all municipalities. The most contaminated samples are: Lagos de Moreno, San Juan de Los Lagos, Union de San Antonio, Villa Hidalgo and, on its last evaluation, San Diego de Alejandria. On the other hand, the municipalities with the lowest pollution are Encarnacion de Diaz, Ojuelos and Teocaltiche.